2020
DOI: 10.29333/ejmste/7801
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Preservice Elementary Teachers’ Subject-Specific Self-Efficacy in Teaching Science

Abstract: Self-efficacy plays a key role in determining teaching practices. Still, concerns regarding the low science self-efficacy beliefs held by elementary teachers have raised questions about the effectiveness of teacher preparation programs. Previous research has been restricted to labeling preservice elementary teachers as having high, medium, or low science teaching self-efficacy. Few extended efforts have been made to clearly distinguish preservice elementary teachers' subjectspecific lack of confidence in teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Informants experience gives them confidence in writing important information, predicting completion steps, and selecting a more systematic settlement method. These findings support previous studies, which found that experience is one of the factors that influence a person's sense of self-efficacy (Al Sultan, 2020;Bandura, 1995;Gao, 2020;Kandil & Işıksal-Bostan, 2018;Sadi & Dağyar, 2015;Šorgo et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…Informants experience gives them confidence in writing important information, predicting completion steps, and selecting a more systematic settlement method. These findings support previous studies, which found that experience is one of the factors that influence a person's sense of self-efficacy (Al Sultan, 2020;Bandura, 1995;Gao, 2020;Kandil & Işıksal-Bostan, 2018;Sadi & Dağyar, 2015;Šorgo et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…For example, a teacher who teaches the subjects of history and mathematics may have higher self-efficacy beliefs in teaching history than in teaching mathematics (possibly because they may have always been more passionate about history). Accordingly, intra-individual differences in self-efficacy beliefs might be found among teachers who teach multiple subjects (Menon and Sadler, 2017 ; Al Sultan, 2020 ). In addition, however, inter-individual differences between teachers of different (groups of) subjects may also be expected (Riggs and Enochs, 1990 ; Welter et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these attempts originate from the most popular measurement instrument in this domain, the STEBI (Riggs and Enochs, 1990 ). This instrument explicitly focuses on science teaching because more global self-assessments (e.g., teaching in general) do not necessarily reflect beliefs about being able to effectively teach science in particular (Al Sultan, 2020 ). The scale is conceptually aligned with Bandura's ( 1986 ) SCT by comprising the two factors of Personal Science Teaching Efficacy (PSTE) and Science Teaching Outcome Expectancy (STOE).…”
Section: Introductionmentioning
confidence: 99%
“…Teachers' attitudes and beliefs in their talent to facilitate meaningful learning experiences directly impact their teaching practices, classroom management, and student outcomes (Berger et al, 2018;Veldman et al, 2020). As science teachers' professional development gains importance, research on teachers' attitudes and beliefs has become educators' focus (Ilhan et al, 2015;2 / 10 Navarro et al, 2022;Sultan, 2020;Yildirim & Tezci, 2016). Teachers' attitudes, interests, and self-efficacies about teaching science significantly impact their ability to teach effectively (Ualesi & Ward, 2018).…”
Section: Introductionmentioning
confidence: 99%